An Empirical Study of the Attention in the Interface of Learning Management System - Patricia Etcheverry; Calixto Alejandro Maldonado; Manuel Pérez Cota (European Alliance for Innovation (EAI), 2015)
This study aims to communicate the preliminary results of the Research taken forward by a UESiglo21 Research Group (Cordoba, Argentina). The same one focuses on the attention as cognitive process of renewed format, linked to the learning, from tools of the Platform Learning Management System (LMS), of two matters of the Bachelor in Computer Science and Software Engineering of the University. The methodological design applied is mixed, called DexPlis, of quantitative and qualitative phases. The quantitative preliminary phase has proved a differential performance of the attention according to support, text and video, from which limits are defined for the qualitative stage in order to interpret the motivations that all the statisticians sublie to, and at the same time, justify the renewed attentional format, framed in an imaginary social effect of the telematic environment, where learning is supported by Information and Communication Technologies (ICT).